Ocenka kacestva vynoslivosti u lyžnikov 15-16 let v usliovijach nikointensivnoj razvivajušcej nagruzk - Gryaznykh, A. V.; Kostyukov, A. V.; Soboleva, E. A. (Zdorov'e celoveka, teorija i metodika fiziceskoj kul'tury i sporta, 2019)
The aim of the research is the analysis of the efficiency of the methodology of the special stamina improvement of racing skiers aged 15-16 in the conditions of training process. Two groups of young men aged 15-16 took part in the research; they have been going in for competitive skiing with qualifications: first senior degree, candidate master of sports. The first group (n=10) (control) has been training according to the standard training plan. The second (n=10) (experienced) - according to a modernized plan, based on the individual approach predominantly, up to 90 %, using developing and low-intensive work-out. At the initial and final stages of the research functional values were defined, which characterized physical capability, training level and the development of special stamina of the sportsmen`s organism: maximum oxygen consumption (PWC170), special load index (SLI), integrative value "stamina coefficient", six-component functional test, Martine test, timed inspiratory capacity test, index of functional changes (IFC), as well as the results of the control and speed trainings and the results of the competitions. The analysis of the efficiency of the methodology of the special stamina improvement of the sportsmen, going in for competitive skiing, has been conducted with the use of the special approaches. The tendency of the improvement of the values, characterizing special and general stamina, has been revealed due to the introduction of the elaborated specialized training plan and individual approach. It is stated that all the studied values, characterizing the level of functional changes of the experienced group, on the whole, have positive tendency, defining the increase of functional capacities, the number of values have significant changes. For the control group the changes are either minimum or absent at all. A negative dynamics is marked, the reasons of which can be a low level of physical work capacity, possible over-training and sportsmen`s illnesses. The results of functional tests and the success of the performance at the competitions prove the acceptance and possibility of the introduction of the proposed methodology, based on the load dosing, the development of aerobic capacities, the individual approach as well as the control of functional values of sportsmen while developing the quality of special stamina. Key words: cross-country skiing, special endurance, competition period, load dosing, intensity zones